PENGARUH PEMBERIAN TEPUNG BUAH KESEMEK (Diospyros kaki var. Junggo) SECARA ORAL TERHADAP PEMBENTUKAN FOAM CELLS DI LAPISAN INTIMA AORTA TIKUS PUTIH (Rattus novergicus strain wistar) YANG DIBERI DIET ATEROGENIK - Arfiani, Eva Putri; Julia, Arliek Rio; Kusumastuty, Inggita (Lembaga Penerbitan Unversitas Esa Unggul, 2017)
Coronary Heart Disease (CVD) is the manifestation of atherosclerosis which is formed of foam cells formation. Beside of medicine, the alternative way to prevent CVD is by high soluble fiber food consumption such as persimmon fruit (Diospyros kaki var. Junggo). The aim of this experiment was to understand the effect of persimmon fruit toward the foam cells formation in the intima aorta layer of rat (Rattus novergicus strain wistar) with atherogenic diet. The experiment was conducted by using experimental laboratoric in vivo with True Experimental Design (Post Test-Only Control Group Design) about 12 weeks, using 5 male rats/group + 1 male rat for spare in each group, the age about 56120 days, and the weight about 100-200 g. The experimental rats were divided into 5 groups, i.e P0 (30.6 g normal diet), P1 (22.9 g atherogenic diet), P2 (22.4 g atherogenic diet + 1.2 g persimmon flour), P3 (21,9 g atherogenic diet + 2.4 g persimmon flour), and P4 (21.4 g atherogenic diet + 3,6 g persimmon flour). Calculation of foam cells was carried out using light microscop with 400x magnification in the area of intima aorta layer of rat. The experiment proved that persimmon flour intervention orally could reduce foam cells formation in the intima aorta layer of white rat with atherogenic diet.Â Keywords: atherogenic diet, persimmon, soluble fiber, foam cells